2012
DOI: 10.1021/bi301247r
|View full text |Cite
|
Sign up to set email alerts
|

Second Double-Stranded RNA Binding Domain of Dicer-like Ribonuclease 1: Structural and Biochemical Characterization

Abstract: Dicer-like ribonuclease III enzymes are involved in different paths related to RNA silencing in plants. Little is known about the structural aspects of these processes. Here we present a structural characterization of the second double-stranded RNA binding domain (dsRBD) of DCL1, which is presumed to participate in pri-micro-RNA recognition and subcellular localization of this protein. We determined the solution structure and found that it has a canonical fold but bears some variation with respect to other hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
(93 reference statements)
0
15
0
2
Order By: Relevance
“…We then determined the binding affinities of both constructs for substrate RNA by means of fluorescence polarization assays (Figure 1 and Table 1 ). We tested two different regions of the miR172a precursor as binding partners, the lower stem region (pri-miR172a-ls), that was previously shown to be essential for the correct processing of miRNA precursors ( 25 ), and the miRNA/miRNA* region (miR172a stem-loop).The affinity of the isolated DCL1-A construct for pri-miR172a fragments is similar to the one determined previously for DCL1-B ( 13 ). DCL1-A RNA binding affinity is somewhat higher for the pri-miR172a-ls construct than for the miR172a stem loop.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…We then determined the binding affinities of both constructs for substrate RNA by means of fluorescence polarization assays (Figure 1 and Table 1 ). We tested two different regions of the miR172a precursor as binding partners, the lower stem region (pri-miR172a-ls), that was previously shown to be essential for the correct processing of miRNA precursors ( 25 ), and the miRNA/miRNA* region (miR172a stem-loop).The affinity of the isolated DCL1-A construct for pri-miR172a fragments is similar to the one determined previously for DCL1-B ( 13 ). DCL1-A RNA binding affinity is somewhat higher for the pri-miR172a-ls construct than for the miR172a stem loop.…”
Section: Resultsmentioning
confidence: 74%
“…More recently, a construct containing the two tandem dsRBDs of DCL1 was shown to complement hyl1–2 mutant plants, further demonstrating the importance of this region in substrate recognition and in the formation of the miRNA processing complex in plants ( 12 ). In a previous work we characterized the second dsRBD of DCL1 from Arabidopsis thaliana (DCL1-B hereafter) ( 13 ). Here we focus on the functional and structural features of the first dsRBD of the same protein.…”
Section: Introductionmentioning
confidence: 99%
“…complement hyl1 phenotypes. By contrast, DCL1-D2 is not a canonical dsRBD, which may leave nucleic acid binding as a vestigial feature during evolution (Burdisso et al, 2012). DCL1-D2 may bind weakly with pri-miRNAs at a sensitivity below R-EMSA (Fig.…”
Section: Differential Functions Of Dsrbds Of Dcl1mentioning
confidence: 99%
“…In this way we can rationalize the similar impact on both function and affinity of both mutations introduced. It was suggested that electrostatic interactions play an important role in dsRBD-RNA recognition [37] , [40] although these effects seem to be dissimilar between different dsRBDs [41] . The absence of alterations in stability on the mutant proteins that could hinder RNA recognition highlight that phosphate backbone recognition is essential for RNA binding by these domains.…”
Section: Discussionmentioning
confidence: 99%